2018
DOI: 10.1016/j.ebiom.2018.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin D2 Receptor DP1 Antibodies Predict Vaccine-induced and Spontaneous Narcolepsy Type 1: Large-scale Study of Antibody Profiling

Abstract: BackgroundNeuropathological findings support an autoimmune etiology as an underlying factor for loss of orexin-producing neurons in spontaneous narcolepsy type 1 (narcolepsy with cataplexy; sNT1) as well as in Pandemrix influenza vaccine-induced narcolepsy type 1 (Pdmx-NT1). The precise molecular target or antigens for the immune response have, however, remained elusive.MethodsHere we have performed a comprehensive antigenic repertoire analysis of sera using the next-generation phage display method - mimotope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 90 publications
1
27
0
Order By: Relevance
“…Recently, the role of DP1R in narcolepsy type 1 patients was investigated. By performing a comprehensive antigenic repertoire analysis of sera from patients, it was found that patients with narcolepsy type 1 exhibit a specific immune response to epitopes of DP1R [152]. These results further support the importance of the L-PGDS-PGD 2 -DP1R pathway in regulating sleep-wake homeostasis [53,153].…”
Section: The L-pgds-pgd 2 -Dp1r Axis In Narcolepsymentioning
confidence: 53%
“…Recently, the role of DP1R in narcolepsy type 1 patients was investigated. By performing a comprehensive antigenic repertoire analysis of sera from patients, it was found that patients with narcolepsy type 1 exhibit a specific immune response to epitopes of DP1R [152]. These results further support the importance of the L-PGDS-PGD 2 -DP1R pathway in regulating sleep-wake homeostasis [53,153].…”
Section: The L-pgds-pgd 2 -Dp1r Axis In Narcolepsymentioning
confidence: 53%
“…However, in order to delve into the background of an individual’s adaptive immune response to a given material, antibody-level information is necessary. For this end, use of mimotope variance analysis [ 10 ] provides a unique opportunity to not only determine the generic responses to new biomaterials, but also patient-specific response to biomaterials, which can guide the development of immune-compatible, patient-specific implant surfaces. Such immunoprofiling based pre-implantation and postimplantation diagnostics can improve the functional outcomes of different implants by aiding in the implant type selection and can also significantly decrease the implant-related complications.…”
Section: Ways Of Achieving Personalizationmentioning
confidence: 99%
“…28 Follow-up studies have not been able to associate HCRTR2 autoantibodies to NT1. 29,30 Other suggested autoantigens in NT1 include prostaglandin D2 receptor 31 and the glutamic acid-isoleucine/α-melanocyte-stimulating hormone, which is a peptide hormone that is cleaved from proopiomelanocortin. 32 Antigen-arrays have previously been used to screen for NT1 autoantigens.…”
Section: Introductionmentioning
confidence: 99%